A heat-insulating, low-dielectric-constant polyaryletherketone-based composite material and a preparation method thereof
By combining porous polyaryletherketone with hollow structure molecular sieve and inorganic perovskite structural materials, and using layered nano-cerium aluminum garnet with hollow structure zeolite molecular sieve with porous PEEK, the medium and low temperature in the aerospace field is solved The instruments and equipment on the bottom of the propellant storage tank are affected by the excessive thermal conductivity of the metal material, which achieves the thermal insulation and low dielectric constant effects of the composite material.
Patent Information
- Application Number
- CN202410402689.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-03
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-04-03
AI Technical Summary
How to make functional composite materials by applying thermal insulation and low dielectric constant to polyaryletherketone to make a functional composite material, and solve the equipment performance of the equipment caused by excessive thermal conductivity of the metal material in the aerospace field Impact issues.
By combining porous polyaryletherketone with hollow structure molecular sieve and inorganic perovskite structural materials, nano-cerium aluminum garnet with layered structures is blended with hollow structure zeolite molecular sieve with porous PEEK and silane coupler The coupling agent is modified to form a composite material with heat insulation and low dielectric constant.
The composite material has a low thermal conductivity and dielectric constant, and has good thermal insulation effect, while avoiding the reduction in equipment performance caused by excessive thermal conductivity.
Smart Images

Figure BDA0004776118240000041 
Figure BDA0004776118240000051 
Figure BDA0004776118240000071
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polyaryletherketone composite materials, and in particular to a heat-insulating, low-dielectric-constant polyaryletherketone-based composite material and a preparation method thereof. Background Art
[0002] In the field of aerospace, most of the installation structures of launch vehicle instruments and equipment are made of metal materials, such as aluminum alloy, carbon steel, etc. The new generation of launch vehicles uses cryogenic propellants such as liquid hydrogen and liquid oxygen. The temperature of liquid hydrogen is about -250°C, and the temperature of liquid oxygen is about -180°C. Metal is a good conductor of heat. If the instruments and equipment on the front bottom of the cryogenic propellant tank are installed with metal materials, the low temperature will be quickly transferred to the instruments and equipment through the metal structure. If the conduction temperature is too low, it will seriously affect the working performance of the instruments and equipment. Therefore, for the above application environment, the equipment material needs to have a certain insulation effect to isolate the temperature transfer, and because it is installed on the instrument and equipment, the material is required to have a certain low dielectric constant.
[0003] Thermoplastic resins represented by polyaryletherketones have become important resin matrices for the preparation of high-performance thermoplastic composites due to their excellent comprehensive properties. They give composites outstanding toughness, aging resistance, fatigue resistance, as well as a series of advantages such as low cost, high efficiency, and recyclability in molding and processing, allowing thermoplastic composites to replace some traditional thermosetting composites and have been successfully applied in high-end industrial fields such as aviation. Among them, the semi-crystalline aromatic thermoplastic engineering plastic polyetheretherketone (PEEK) is one of the most important varieties of commercial polyaryletherketone materials. Its repeating structural unit is "—C6H4—O—C6H4—O—C6H4—CO—", which has excellent properties such as high temperature resistance, wear resistance, dimensional stability, flame retardancy, and chemical resistance. It has very broad application prospects in aerospace, automobile manufacturing, energy development, electronics and electrical, and medical fields.
[0004] How to impart both thermal insulation effect and low dielectric effect to polyaryletherketone to prepare a functional composite material is a technical problem to be solved by the present invention. Summary of the invention
[0005] In order to solve the above technical problems, a heat-insulating, low-dielectric-constant polyaryletherketone-based composite material and a preparation method thereof are provided. The porous polyaryletherketone is combined with a hollow structure molecular sieve and an inorganic perovskite structure material to obtain a heat-insulating, low-dielectric-constant polyaryletherketone-based composite material having a lower thermal conductivity and dielectric constant.
[0006] In order to achieve the above objectives, the present invention is implemented by the following technical solutions:
[0007] A heat-insulating, low-dielectric-constant polyaryletherketone-based composite material, comprising 100% by weight of the following materials: 1-5% of a hollow-structured zeolite molecular sieve, 3-15% of nano-cerium aluminum garnet, and the remainder being porous polyaryletherketone;
[0008] The hollow structure molecular sieve has a hollow interior and a shell layer of at least one layer of zeolite molecular sieve.
[0009] Furthermore, the particle size of the hollow structure zeolite molecular sieve is less than 800 mesh; and the particle size of the nano cerium aluminum garnet is less than 500 nm.
[0010] Furthermore, the method for obtaining the hollow structure zeolite molecular sieve is:
[0011] S1, using polystyrene microspheres as templates, first immersing the polystyrene microspheres in a cationic polymer solution for adsorption, washing with water after solid-liquid separation, and then immersing the polystyrene microspheres in an anionic polymer solution for adsorption, washing with water after solid-liquid separation, and cyclically immersing and adsorbing multiple times in this order until the last immersion and adsorption of the cationic polymer solution, washing with water after solid-liquid separation to obtain a positively charged layer-by-layer assembly template;
[0012] S2. The positively charged layer-by-layer assembly template is first immersed in a nano-zeolite colloidal solution for adsorption, washed with water after solid-liquid separation, and then immersed in a cationic polymer solution for adsorption, washed with water after solid-liquid separation. The adsorption is cycled multiple times in this order until the last time of immersion and adsorption in a cationic polymer solution, washed with water after solid-liquid separation to obtain a layer-by-layer assembly zeolite hollow precursor template, dried at room temperature, calcined, and cooled to obtain a hollow structure zeolite molecular sieve.
[0013] Preferably, the diameter of the polystyrene microspheres in S1 is 0.5-2.5 μm; the ratio of the amount of the polystyrene microspheres to the amount of the impregnation adsorption solution is 5-15 g / L; the cationic polymer solution contains water and a cationic polymer with a concentration of 0.5-1.5 g / L, and 0.05-0.1 mol / L sodium chloride; the anionic polymer solution contains water and an anionic polymer with a concentration of 0.5-1.5 g / L, and 0.05-0.1 mol / L sodium chloride; the number of layers of the positively charged layer-by-layer assembly template is an odd number of layers between 2 and 10;
[0014] The mass concentration of the nano zeolite colloidal solution in S2 is 3-8%, the ratio of the amount of the positively charged layer-by-layer assembly template to the amount of the impregnation adsorption solution is 5-15 g / L; the number of layers of the positively charged layer-by-layer assembly template is an odd number of 2-10 layers; the calcination process is: heating to 550-650° C., calcining for 3-5 hours in a nitrogen atmosphere, and then calcining for 6-10 hours in an air atmosphere;
[0015] The immersion adsorption time in S1 and S2 was 10-30 min, respectively.
[0016] More preferably, the cationic polymer is selected from one of polydiallyldimethylammonium chloride (PDADMAC), polyacryloyloxyethyltrimethylammonium chloride (PADAM-Cl), polymethacryloyloxyethyltrimethylammonium chloride (PMADAM-Cl), polyacrylamide-N-propyltrimethylammonium chloride (PAPTAC), polymethacrylamidepropyltrimethylammonium chloride (PMAPTAC), polylysine, polydopamine, and chitosan; and the anionic polymer is selected from one of polyacrylamide (PAM), sodium polyacrylate (PAAS), sodium polymethacrylate (PMA), and sodium polystyrene sulfonate (PSSS).
[0017] Furthermore, the porous polyaryletherketone is a porous structure formed by using one or more of polyetheretherketone, polyetherketone, polyetherketoneketone, and polyetherketoneetherketoneketone as a matrix; conventional concentrated sulfuric acid etching can be used, for example, according to the implementation described in Chinese patent publication number CN116041901B.
[0018] The method for preparing the above-mentioned heat-insulating, low-dielectric-constant polyaryletherketone-based composite material comprises the following steps:
[0019] (1) heating and mixing the hollow structure zeolite molecular sieve and part of the porous polyaryletherketone under mechanical stirring, then adding a silane coupling agent, continuing to heat and mix, mixing evenly, and melt-blending and extruding to obtain a first pellet for standby use;
[0020] (2) heating and mixing the nano-cerium aluminum garnet and the remaining part of the porous polyaryletherketone under mechanical stirring, then adding a silane coupling agent, continuing to heat and mix, mixing evenly, and melt-blending and extruding to obtain a second pellet for standby use;
[0021] (3) The first pellets and the second pellets are mixed evenly, and then melt-blended, extruded and granulated to obtain a heat-insulating, low-dielectric-constant polyaryletherketone-based composite material.
[0022] Furthermore, the conditions for heating and mixing under mechanical stirring are: stirring speed 500-1500rpm, heating temperature 40-80°C, mixing time 10-30min; the silane coupling agent is conventionally used, such as KH550, KH560, KH570, etc., and the amount used is 3-8% of the weight of nano cerium aluminum garnet or hollow structure zeolite molecular sieve.
[0023] Furthermore, the melt blending is carried out using a twin-screw extruder, and the specific parameter settings are: zone one 250-370°C, zone two 280-410°C, zone three to zone six 280-410°C, zone seven 280-420°C, head temperature 280-420°C, screw speed 200-500rpm, and feeding frequency 10-15Hz.
[0024] Beneficial technical effects:
[0025] The present invention adopts layered nano cerium aluminum garnet and hollow structure zeolite molecular sieve of specific configuration, and respectively blends and extrude the two with porous PEEK. When the silane coupling agent is used to modify the mixture, the two are respectively hidden in the holes of the porous PEEK, and the two are respectively preliminarily melt-blended to form a first pellet and a second pellet, and then the first pellet and the second pellet are melt-blended to obtain the composite material of the present invention; since the nano cerium aluminum garnet has a layered structure and the hollow structure zeolite molecular sieve has an internal hollow structure and external fine pores, after the two pellets are combined, the nano cerium aluminum garnet forms an effective heat-insulating connection system for the hollow structure zeolite molecular sieve under the premise of uniform blending and distribution, and the combination of the layered structure and the hollow structure enables the composite material to have a better heat-insulating effect and a lower dielectric constant. DETAILED DESCRIPTION
[0026] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is by no means intended to limit the present invention and its application or use. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0027] Unless otherwise specifically stated, the numerical value set forth in these embodiments does not limit the scope of the present invention. The technology and method known to those of ordinary skill in the relevant art may not be discussed in detail, but in appropriate cases, the technology and method should be considered as a part of the specification. In all examples shown and discussed here, any specific value should be interpreted as being merely exemplary, rather than as a limitation. Therefore, other examples of exemplary embodiments may have different values.
[0028] The experimental methods in the following examples without specifying specific conditions are usually measured in accordance with national standards; if there is no corresponding national standard, the method is carried out in accordance with the general standard requirements or general methods.
[0029] Preparation Example 1
[0030] This case is the preparation of hollow structure zeolite molecular sieve. The specific preparation method is as follows:
[0031] S1. Using polystyrene microspheres (PS) as templates, the polystyrene microspheres are first immersed in a cationic polymer solution (abbreviated as C solution in the following table) for adsorption, washed with water after solid-liquid separation, and then immersed in an anionic polymer solution (abbreviated as A solution in the following table) for adsorption, washed with water after solid-liquid separation, and the adsorption is repeated multiple times in this order until the last immersion and adsorption of the cationic polymer solution, washed with water after solid-liquid separation to obtain a positively charged layer-by-layer assembly template;
[0032] S2. The positively charged layer-by-layer assembly template is first immersed in a nano zeolite colloidal solution (abbreviated as Z liquid in the table below) for adsorption, washed with water after solid-liquid separation, and then immersed in a cationic polymer solution (the same as C liquid used in S1) for adsorption, washed with water after solid-liquid separation, and the adsorption is repeated multiple times in this order until the last time of immersion and adsorption of the cationic polymer solution, washed with water after solid-liquid separation to obtain a layer-by-layer assembly zeolite hollow precursor template, dried at room temperature, calcined, and cooled to obtain a hollow structure zeolite molecular sieve (expressed as HMS).
[0033] Specific preparation parameters are shown in Table 1 below:
[0034] Table 1 Specific preparation parameters of hollow structure zeolite molecular sieve
[0035]
[0036]
[0037] Preparation Example 2
[0038] This case is the preparation of porous PEEK: weigh 1000g of PEEK particles (model PEEK5600G, particle diameter not exceeding 3.5mm) for use; pour 1200mL of concentrated sulfuric acid with a mass concentration of 70% into a three-necked flask, set the ultrasonic dispersion power to 150W, the heating temperature to 100°C, and add PEEK particles in 5 batches, with 200g added in each batch, and the time interval is 1min. After all the particles are added, condense and reflux for 20min to terminate the etching reaction, pour out the concentrated sulfuric acid (which can be recycled and reused), wash and filter the PEEK particles 3 times with deionized water, and dry them in an oven at 100°C for 5h. After drying, porous PEEK particles are obtained for use in the following embodiments.
[0039] Example 1
[0040] A heat-insulating, low-dielectric-constant polyaryletherketone-based composite material, comprising the following materials in 100% by weight: 3% of the HMS-Ⅰ hollow structure zeolite molecular sieve of Preparation Example 1, 15% of nano-cerium aluminum garnet, and the balance of 82% of porous PEEK particles (specific amount of porous PEEK particles 820g); the particle size of the hollow structure zeolite molecular sieve is less than 800 mesh; the particle size of the nano-cerium aluminum garnet is less than 500nm;
[0041] The preparation method of the heat-insulating, low-dielectric-constant polyaryletherketone-based composite material of this case comprises the following steps:
[0042] (1) The hollow structure zeolite molecular sieve and half of the porous PEEK particles were heated and mixed under mechanical stirring (stirring speed 1000 rpm, heating temperature 60°C), and then KH550 was added (the amount of KH550 was 5% of the weight of the hollow structure zeolite molecular sieve), and the mixture was heated and mixed for 20 minutes. The mixture was evenly mixed, and the melt blending extrusion was carried out using a twin-screw extruder. The specific parameter settings were: 350°C for zone 1, 360±5°C for zones 2 to 6, 375°C for zone 7, and head temperature 380°C; the screw speed was 400 rpm, and the feeding frequency was 10 Hz, to obtain the first pellets for standby use;
[0043] (2) The nano-cerium aluminum garnet and the remaining amount of porous PEEK particles are heated and mixed under mechanical stirring (stirring speed 1000 rpm, heating temperature 60° C.), and then KH550 is added (the amount of KH550 is 5% of the weight of the hollow structure zeolite molecular sieve), and the heating and mixing are continued for 20 minutes. The mixture is mixed evenly, and the melt blending and extrusion conditions are the same as those in step (1) to obtain a second pellet, which is set aside;
[0044] (3) The first pellets and the second pellets are mixed evenly, and then melt-blended and extruded to form pellets. The melt-blending and extrusion conditions are the same as those in step (1), so as to obtain a heat-insulating, low-dielectric-constant polyaryletherketone-based composite material.
[0045] Example 2
[0046] A heat-insulating, low-dielectric-constant polyaryletherketone-based composite material, comprising the following materials in 100% by weight: 4% of the HMS-Ⅱ hollow structure zeolite molecular sieve of Preparation Example 1, 8% of nano-cerium aluminum garnet, and the balance of 88% of porous PEEK particles (specific amount of porous PEEK particles 880g); the particle size of the hollow structure zeolite molecular sieve is less than 800 mesh; the particle size of the nano-cerium aluminum garnet is less than 500nm;
[0047] The preparation method of the heat-insulating, low-dielectric-constant polyaryletherketone-based composite material of this case comprises the following steps:
[0048] (1) The hollow structure zeolite molecular sieve and half of the porous PEEK particles were heated and mixed under mechanical stirring (stirring speed 800 rpm, heating temperature 80° C.), and then KH560 was added (the amount of KH560 was 3% of the weight of the hollow structure zeolite molecular sieve), and the mixture was heated and mixed for 30 min. The mixture was mixed evenly, and the melt blending extrusion was carried out using a twin-screw extruder. The specific parameters were set as follows: 350° C. for zone 1, 360±5° C. for zones 2 to 6, 375° C. for zone 7, and 380° C. for die head temperature; the screw speed was 400 rpm, and the feeding frequency was 10 Hz. The first pellets were obtained and set aside;
[0049] (2) The nano-cerium aluminum garnet and the remaining amount of porous PEEK particles are heated and mixed under mechanical stirring (stirring speed 800 rpm, heating temperature 80° C.), and then KH560 is added (the amount of KH560 is 3% of the weight of the hollow structure zeolite molecular sieve), and the heating and mixing are continued for 30 minutes. The mixture is mixed evenly, and the melt blending and extrusion conditions are the same as those in step (1) to obtain a second pellet, which is set aside;
[0050] (3) The first pellets and the second pellets are mixed evenly, and then melt-blended and extruded to form pellets. The melt-blending and extrusion conditions are the same as those in step (1), so as to obtain a heat-insulating, low-dielectric-constant polyaryletherketone-based composite material.
[0051] Example 3
[0052] A heat-insulating, low-dielectric-constant polyaryletherketone-based composite material, comprising the following materials in 100% by weight: 5% of the HMS-Ⅲ hollow structure zeolite molecular sieve of Preparation Example 1, 5% of nano-cerium aluminum garnet, and the balance of 90% of porous PEEK particles (specific amount of porous PEEK particles is 900g); the particle size of the hollow structure zeolite molecular sieve is less than 800 mesh; the particle size of the nano-cerium aluminum garnet is less than 500nm;
[0053] The preparation method of the heat-insulating, low-dielectric-constant polyaryletherketone-based composite material of this case comprises the following steps:
[0054] (1) The hollow structure zeolite molecular sieve and half of the porous PEEK particles were heated and mixed under mechanical stirring (stirring speed 1200 rpm, heating temperature 70°C), and then KH570 was added (the amount of KH570 was 8% of the weight of the hollow structure zeolite molecular sieve), and the mixture was heated and mixed for 15 minutes. The mixture was evenly mixed, and the melt blending extrusion was carried out using a twin-screw extruder. The specific parameter settings were: 350°C for zone 1, 360±5°C for zones 2 to 6, 375°C for zone 7, and head temperature 380°C; the screw speed was 400 rpm, and the feeding frequency was 10 Hz, to obtain the first pellets for standby use;
[0055] (2) The nano-cerium aluminum garnet and the remaining amount of porous PEEK particles are heated and mixed under mechanical stirring (stirring speed 1200 rpm, heating temperature 70° C.), and then KH570 is added (the amount of KH570 is 8% of the weight of the hollow structure zeolite molecular sieve), and the heating and mixing are continued for 15 minutes. The mixture is mixed evenly, and the melt blending and extrusion conditions are the same as those in step (1) to obtain a second pellet, which is set aside;
[0056] (3) The first pellets and the second pellets are mixed evenly, and then melt-blended and extruded to form pellets. The melt-blending and extrusion conditions are the same as those in step (1), so as to obtain a heat-insulating, low-dielectric-constant polyaryletherketone-based composite material.
[0057] Comparative Example 1
[0058] The composite material of this case does not contain hollow structure zeolite molecular sieve, that is, nano cerium aluminum garnet accounts for 18% of the composite material, and is prepared according to step (2) of Example 1.
[0059] Comparative Example 2
[0060] The composite material of this case does not contain nano-cerium aluminum garnet, that is, the hollow structure zeolite molecular sieve accounts for 18% of the composite material, and is prepared according to step (1) of Example 1.
[0061] Comparative Example 3
[0062] The preparation of the composite material in this case is the same as that in Example 1, except that the hollow structure zeolite molecular sieve is replaced by silica aerogel.
[0063] The above composite materials were subjected to performance tests, and the test results are shown in Table 2.
[0064] Table 2 Composite material properties
[0065]
[0066]
[0067] The present invention respectively blends and extrude the two with porous PEEK. When the silane coupling agent modifies the mixture, the two are respectively hidden in the holes of the porous PEEK. The two are respectively melt-blended to form a first pellet and a second pellet. The first pellet and the second pellet are then melt-blended to form a composite material. Since the nano-cerium aluminum garnet has a layered structure and the hollow-structured zeolite molecular sieve has an internal hollow structure and external fine pores, after the two pellets are combined, the nano-cerium aluminum garnet forms an effective thermal insulation connection system for the hollow-structured zeolite molecular sieve under the premise of uniform blending and distribution. The combination of the layered structure and the hollow structure enables the composite material to have a better thermal insulation effect and a lower dielectric constant. Using nano-cerium aluminum garnet alone can not effectively reduce the dielectric constant, and using zeolite molecular sieve with hollow structure alone can effectively reduce the dielectric constant, but the insulation effect is similar to that of using nano-cerium aluminum garnet, and because the preparation process of zeolite molecular sieve with hollow structure is complicated, it is not desirable to add a large amount of zeolite molecular sieve with hollow structure in the matrix, so the two are combined, and a relatively small amount of zeolite molecular sieve with hollow structure is combined with a relatively large amount of nano-cerium aluminum garnet, so that the composite material can achieve the best insulation effect and dielectric constant. The aerogel structure in comparative example 3 is loose, and there may be a situation where the aerogel skeleton structure is destroyed during blending, so the insulation effect is not good. The zeolite molecular sieve with hollow structure can reduce the damage to its structure during screw extrusion due to its hiding in porous PEEK first, and the subsequent blending time with nano-cerium aluminum garnet / PEEK pellets, a large amount of layered nano-cerium aluminum garnet has a certain protective effect on the zeolite molecular sieve with hollow structure, which reduces the damage to the hollow structure, so the combination of the two has a better insulation effect.
[0068] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A heat-insulating, low-dielectric-constant polyaryletherketone-based composite material, characterized in that: The invention comprises the following materials in an amount of 100% by weight: 1-5% of hollow structure zeolite molecular sieve, 3-15% of nano cerium aluminum garnet, and the balance of porous polyaryletherketone; The particle size of the hollow structure zeolite molecular sieve is less than 800 mesh; the particle size of the nano cerium aluminum garnet is less than 500nm; The hollow structure zeolite molecular sieve has a hollow interior and a shell layer of at least one layer of zeolite molecular sieve; The method for obtaining the hollow structure zeolite molecular sieve is: S1, using polystyrene microspheres as templates, first immersing the polystyrene microspheres in a cationic polymer solution for adsorption, washing with water after solid-liquid separation, and then immersing the polystyrene microspheres in an anionic polymer solution for adsorption, washing with water after solid-liquid separation, and cyclically immersing and adsorbing multiple times in this order until the last immersion and adsorption of the cationic polymer solution, washing with water after solid-liquid separation to obtain a positively charged layer-by-layer assembly template; S2, immersing the positively charged layer-by-layer assembly template in a nano-zeolite colloidal solution for adsorption, washing with water after solid-liquid separation, and then immersing in a cationic polymer solution for adsorption, washing with water after solid-liquid separation, and cyclically immersing and adsorbing in this order until the last immersion and adsorption of the cationic polymer solution, washing with water after solid-liquid separation to obtain a layer-by-layer assembly zeolite hollow precursor template, drying at room temperature, calcining, and cooling to obtain a hollow structure zeolite molecular sieve; The diameter of the polystyrene microspheres in S1 is 0.5-2.5 μm; the ratio of the amount of the polystyrene microspheres to the amount of the impregnation adsorption solution is 5-15 g / L; the cationic polymer solution contains water and a cationic polymer with a concentration of 0.5-1.5 g / L, and 0.05-0.1 mol / L sodium chloride; the anionic polymer solution contains water and an anionic polymer with a concentration of 0.5-1.5 g / L, and 0.05-0.1 mol / L sodium chloride; the number of layers of the positively charged layer-by-layer assembly template is an odd number of layers between 2 and 10; The mass concentration of the nano zeolite colloidal solution in S2 is 3-8%, the ratio of the amount of the positively charged layer-by-layer assembly template to the amount of the impregnation adsorption solution is 5-15 g / L; the number of layers of the layer-by-layer assembly zeolite hollow precursor template is an even number of 4-10 layers; the calcination process is: heating to 550-650°C, calcining for 3-5 hours in a nitrogen atmosphere, and then calcining for 6-10 hours in an air atmosphere; The immersion adsorption time in S1 and S2 was 10-30 min, respectively.
2. A heat-insulating, low-dielectric-constant polyaryletherketone-based composite material according to claim 1, characterized in that: The cationic polymer is selected from one of polydiallyldimethylammonium chloride, polyacryloyloxyethyltrimethylammonium chloride, polymethacryloyloxyethyltrimethylammonium chloride, polyacrylamide-N-propyltrimethylammonium chloride, polymethacrylamidepropyltrimethylammonium chloride, polylysine, polydopamine, and chitosan; the anionic polymer is selected from one of polyacrylamide, sodium polyacrylate, sodium polymethacrylate, and sodium polystyrene sulfonate.
3. A heat-insulating, low-dielectric-constant polyaryletherketone-based composite material according to any one of claims 1 to 2, characterized in that: The porous polyaryletherketone is formed into a porous structure by using one or more of polyetheretherketone, polyetherketone, polyetherketoneketone and polyetherketoneetherketoneketone as a matrix.
4. A method for preparing a heat-insulating, low-dielectric-constant polyaryletherketone-based composite material according to any one of claims 1 to 2, characterized in that: The steps include: (1) heating and mixing the hollow structure zeolite molecular sieve and part of the porous polyaryletherketone under mechanical stirring, then adding a silane coupling agent, continuing to heat and mix, mixing evenly, and melt-blending and extruding to obtain a first pellet for standby use; (2) heating and mixing the nano-cerium aluminum garnet and the remaining part of the porous polyaryletherketone under mechanical stirring, then adding a silane coupling agent, continuing to heat and mix, mixing evenly, and melt-blending and extruding to obtain a second pellet for standby use; (3) The first pellets and the second pellets are mixed evenly, and then melt-blended, extruded and granulated to obtain a heat-insulating, low-dielectric-constant polyaryletherketone-based composite material.
5. The preparation method according to claim 4, characterized in that: The conditions for heating and mixing under mechanical stirring are: stirring speed 500-1500 rpm, heating temperature 40-80° C., and mixing time 10-30 min.
6. The preparation method according to claim 4, characterized in that: The melt blending is carried out by a twin-screw extruder, and the specific parameter settings are: zone 1 250-370°C, zone 2 280-410°C, zone 3 to zone 6 280-410°C, zone 7 280-420°C, die head temperature 280-420°C, screw speed 200-500rpm, and feeding frequency 10-15Hz.
Citation Information
Patent Citations
A PEEK alloy and its preparation method
CN116041901B
Microporous zeolite material modified PEEK and its preparation method
CN102399413A
Yttrium-cerium-aluminum garnet phosphor and light-emitting device
CN103173219A
Process of preparing hollow zeolite microsphere
CN1506308A